2016
DOI: 10.4172/2155-9570.1000583
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Porcine Lens Storage Methods for Optimal Phacoemulsification

Abstract: Objective: The study purpose was to compare effects of two porcine lens storage methods on phacoemulsification efficiency and chatter.Methods: This in vitro laboratory study was conducted at the John A. Moran Eye Center Laboratories, University of Utah. Porcine nuclei were fixed in 10% formaldehyde and cut into 2.0 mm cubes. An equal number of lens cubes either were stored in a 100% humidity chamber or were partially immersed in balanced salt solution (BSS). Using identical parameters on the phacoemulsificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The lenses were rinsed three times with a balanced salt solution (BSS) and then immersed completely in BSS for storage at room temperature for 24 hours. 9 Lenses were used within 24 hours of formalin fixation. Care was taken during the extractions to preserve both the cortex and nuclei of the lenses to ensure uniform lens hardening.…”
Section: Lens Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The lenses were rinsed three times with a balanced salt solution (BSS) and then immersed completely in BSS for storage at room temperature for 24 hours. 9 Lenses were used within 24 hours of formalin fixation. Care was taken during the extractions to preserve both the cortex and nuclei of the lenses to ensure uniform lens hardening.…”
Section: Lens Preparationmentioning
confidence: 99%
“…Crushing studies have shown that lenses prepared by this method are comparable to grade 3-4+ human cataractous lenses. 9,10 Surgical Procedures: Grooving Efficiency with Increasing Flow Rates Sixty porcine lenses were selected at random following the lens hardening process. Each lens was placed individually in a groover device developed at the Moran Eye Center.…”
Section: Lens Preparationmentioning
confidence: 99%